Isolation and characterization of useful mutants induced by gamma irradiation in ’Kranti’ indian mustard (Brassica juncea) - BAI, B; KUMAR, H (The Indian Journal of Agricultural Sciences, 2013)
Genetic variability was induced, in the ’Kranti’ Indian mustard [Brassica/juncea (L.) Czemj. & Cosson]. utilizing 30,40 and 50 kr doses of gamma-ray Irradiation. ’In M 3 generation, compared wuh the econtrol, substantial decrease was observed in the mean value of various quantitative charactcers in the mutagen-treated populations. More variution was induced at 30 kr compared with that at 40 or 50 kr dose. Four mutants were identified ar 30 kr dose, which besides being early in maturity, gave better yield also-compared with the control. The better seed yield of the transmutated plants was due either to intcrease in seed weight or to increse in number of siliquae/plant.